Impact of 24-h Cooling Prior to Freezing on the Survival of Domestic Cat (Felis catus) Epididymal Sperm - Martins, J. L. A. [UNESP]; Villaverde, A. I. S. B.; Lima, A. F. M. [UNESP]; Steagall, P. V. M. [UNESP]; Ferreira, João Carlos Pinheiro [UNESP]; Taconeli, C. A. [UNESP]; Lopes, Maria Denise [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
The aim of this study was to investigate the impact of a 24-h cooling period prior to freezing on domestic cat epididymal sperm viability. Fifteen tomcats were submitted to routine orchiectomy and sperm samples were retrieved from both epididymides in a Tris-glucose-20% egg yolk extender. For each tomcat, the diluted sperm was split into two equal volumes and cooled to 5 degrees C at a rate of 0.5 degrees C/min; one sample for 60 min (control) and the other for 24 h (cooled). After the cooling period, samples from both groups were frozen using an identical freezing protocol. Sperm samples were evaluated in three different periods: immediately after harvesting, after cooling at 5 degrees C for 24 h (cooled group) and after freezing thawing of control and cooled groups. Evaluations consisted of sperm motility and progressive status, sperm morphology and plasma membrane integrity (PMI) using two fluorescent probes. After cooling for 24 h, a decrease (p < 0.05) in sperm motility, progressive status and PMI was observed when compared to sperm samples immediately after collection. Comparing the results obtained after thawing, no difference (p < 0.05) was found regarding sperm motility, progressive status, PMI and sperm morphology between control and cooled groups. The results from the present study show that cooling cat epididymal spermatozoa at 5 degrees C for 24 h prior to freezing does not lead to major damage of spermatozoa impairing the freeze-thaw process.